Reorienting the Pure Land Nisei Buddhism in the Transwar Years, 1943-1965 - Masatsugu, Michael Kenji (Intersections: Asian and Pacific American Transcultural Studies, 2023)
Post-World War II historical developments, including Japanese American resettlement, the U.S. occupation of Japan, the Cold War, and decolonization in an emerging "Third World," created both a climate of uncertainty and possibility for the future of Japanese American Buddhism in the United States. As both a racial minority and as adherents of a non-Christian religious tradition with roots in Asia, Nikkei Buddhists faced distinct challenges in asserting their religion as part of their ethnic heritage. Adaptations associated with Nisei Buddhism sought to prioritize cultural assimilation as prescribed by U.S. government officials and other proponents of racial liberalism, while also seeking to maintain Shin Buddhist tradition, claiming it as integral to Nikkei heritage and part of a tradition of American religious freedom.